Molecular Mechanism for the Shp-2 Tyrosine Phosphatase Function in Promoting Growth Factor Stimulation of Erk Activity - Shi, Zhong-Qing (American Society for Microbiology, 2000)
We have previously shown that activation of extracellular signal-regulated kinase (Erk) by epidermal growth factor (EGF) treatment was significantly decreased in mouse fibroblast cells expressing a mutant Shp-2 molecule lacking 65 amino acids in the SH2-N domain, Shp-2(Δ46-110). To address the molecular mechanism for the positive role of Shp-2 in mediating Erk induction, we evaluated the activation of signaling components upstream of Erk in Shp-2 mutant cells. EGF-stimulated Ras, Raf, and Mek activation was significantly attenuated in Shp-2 mutant cells, suggesting that Shp-2 acts to promote Ras activation or to suppress the down-regulation of activated Ras. Biochemical analyses indicate that upon EGF stimulation, Shp-2 is recruited into a multiprotein complex assembled on the Gab1 docking molecule and that Shp-2 seems to exert its biological function by specifically dephosphorylating an unidentified molecule of 90 kDa in the complex. The mutant Shp-2(Δ46-110) molecule failed to participate in the Gab1-organized complex for dephosphorylation of p90, correlating with a defective activation of the Ras-Raf-Mek-Erk cascade in EGF-treated Shp-2 mutant cells. Evidence is also presented that Shp-2 does not appear to modulate the signal relay from EGF receptor to Ras through the Shc, Grb2, and Sos proteins. These results begin to elucidate the mechanism of Shp-2 function downstream of a receptor tyrosine kinase to promote the activation of the Ras-Erk pathway, with potential therapeutic applications in cancer treatment.